A Prospective Study On Pathology Distribution Of Dizziness Patients In Neuro-Otology Department At National Hospital For Neurology & Neurosurgery, Queen Square, London - Zuraidah Zainun; Davies RA; Marti (Talenta Publisher, 2020)
Abstract. â€œDizzinessâ€ is a general term [1] and covers a variety of â€˜abnormal sensations relating to perception of the bodyâ€™s relationship to spaceâ€™ [2]. According to the previous paper, Drachman and Hart [3] dizziness can be divided into four subtypes: vertigo, presyncope lightheadedness, disequilibrium, and other dizziness. Among all these subtypes, vertigo is one of the most commonly reported symptoms by the vestibular disordered patient nowadays [1]. Globally dizziness is one of â€˜the common, chronic and untreated symptomsâ€™ among the population in the age range of 18-65 years old. [4]. aims: To assess the pathology distribution among dizziness patients in NHNH. Method: All 97 patients were selected from an age range of 18-75 years, with a mean age of 47.92 (S.D=13.17). Method: All 97 patients were selected from an age range of 18-75 years, with a mean age of 47.92 (S.D=13.17). They were asked to fill in the VSS and MVSS questionnaires.Â Results:Â We were able to invite all 109 patients to participate our study within the 39 days (13 November â€“ 21 December 2007) thatâ€™s attended the Neuro-otology clinic, NHNN. Conclusion: In this study it has been found that women commonly presented with the dizziness symptoms compared to men. Keyword: modified vertigo symptom scale, pathology, vertigo symptom scale, vestibular disordered